Microstructure of the Corpus Callosum Long after Pediatric Concussion. (18th September 2020) - Sohn, Maya N.; Virani, Shane; Carlson, Helen L.; MacPhail, Shelby; Low, Trevor A.; Plourde, Vickie; Yeates, Keith Owen; Lebel, Catherine; Brooks, Brian L.
Abstract: Objective: The long-term effects of pediatric concussion on white matter microstructure are poorly understood. This study investigated long-term changes in white matter diffusion properties of the corpus callosum in youth several years after concussion. Methods: Participants were 8–19 years old with a history of concussion (n = 36) or orthopedic injury (OI) (n = 21). Mean time since injury for the sample was 2.6 years (SD = 1.6). Participants underwent diffusion magnetic resonance imaging, completed cognitive testing, and rated their post-concussion symptoms. Measures of diffusivity (fractional anisotropy, mean, axial, and radial diffusivity) were extracted from white matter tracts in the genu, body, and splenium regions of the corpus callosum. The genu and splenium tracts were further subdivided into 21 equally spaced regions along the tract and diffusion values were extracted from each of these smaller regions. Results: White matter tracts in the genu, body, and splenium did not differ in diffusivity properties between youth with a history of concussion and those with a history of OI. No significant group differences were found in subdivisions of the genu and splenium after correcting for multiple comparisons. Diffusion metrics did not significantly correlate with symptom reports or cognitive performance. Conclusions: These findings suggest that at approximately 2.5 years post-injury, youth with prior concussion do not have differences in their corpus callosum microstructure compared to youth with OI. Although these results are promising from the perspective of long-term recovery, further research utilizing longitudinal study designs is needed to confirm the long-term effects of pediatric concussion on white matter microstructure.